2013
DOI: 10.1016/j.fsi.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Mytilus galloprovincialis to bacterial challenges by metabolomics and proteomics

Abstract: a b s t r a c tPathogens can cause diseases and lead to massive mortalities of aquaculture animals and substantial economic loss. In this work, we studied the responses induced by Micrococcus luteus and Vibrio anguillarum in gill of mussel Mytilus galloprovincialis at protein and metabolite levels. Metabolic biomarkers (e.g., amino acids, betaine, ATP) suggested that both M. luteus and V. anguillarum induced disturbances in energy metabolism and osmotic regulation. The unique and some more remarkably altered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Polar metabolites were extracted from the gills of clams as previously described (Ji et al, 2013). Briefly, the gill tissue was homogenized in 82.5% methanol in water at a solvent/tissue ratio of 4.85:1, using a Precellys 24 high throughput homogenizer (Berta, France).…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…Polar metabolites were extracted from the gills of clams as previously described (Ji et al, 2013). Briefly, the gill tissue was homogenized in 82.5% methanol in water at a solvent/tissue ratio of 4.85:1, using a Precellys 24 high throughput homogenizer (Berta, France).…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…With the development of system biology techniques (genomics, transcriptomics, proteomics and metabolomics), researchers have applied these eomic approaches to fish and shellfish immunology, which can provide a comprehensive understanding of immune responses of marine aquaculture animals to pathogen challenges [11,12]. Recently, Ji et al reported the proteomic responses in M. galloprovincialis challenged by another vibrio, V. anguillarum [12].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of system biology techniques (genomics, transcriptomics, proteomics and metabolomics), researchers have applied these eomic approaches to fish and shellfish immunology, which can provide a comprehensive understanding of immune responses of marine aquaculture animals to pathogen challenges [11,12]. Recently, Ji et al reported the proteomic responses in M. galloprovincialis challenged by another vibrio, V. anguillarum [12]. They found that the infection of V. anguillarum caused disruption in energy metabolism and oxidative stress in M. galloprovincialis, indicated by the proteomic biomarkers, including procollagen-proline dioxygenase, protein disulfide isomerase, nucleoside diphosphate kinases, electron transfer flavoprotein and glutathione S-transferase [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinate is a tricarboxylic acid cycle (TCA) intermediate and is capable of donating electrons to the electron transport chain via oxidation to fumarate by succinate dehydrogenase (SDH). Decreased expression of SDH and increased levels of succinate are indicative of oxidative stress in shellfish when oxygen availability is limited (Tuffnail et al 2009 ;Anestis et al 2010 ;Connor and Gracey 2012 ), and when organisms are exposed to toxins (Wu et al 2013a ;Hanana et al 2014 ) or pathogens (Ji et al 2013 ;Wu et al 2013b ). Elevated tissue concentrations of succinate are also indicative of poor larval quality due to lower capacity for energy production (Young et al 2015b ).…”
Section: Discussionmentioning
confidence: 99%